The Effect of Adolescent Assertive Ability Training on The Prevention of Smoking Behavior - Fatimah, Siti (Psychosophia: Journal of Psychology, Religion, and Humanity, 2024)
Teenagers who tend to prioritize emotional considerations over rational ones cause an increase in Indonesian teenager's smoking rate. Apart from that, teenagers' experiences of receiving praise or ridicule from friends when smoking or not smoking and the desire to be accepted by the environment are the emotional reasons teenagers start smoking. In this case, efforts can be made to prevent smoking behavior by providing assertiveness training to teenagers. This research aims to see the difference in influence before and after being given assertive training on students. This research used an experimental research method with a one group pretest-posttest design. The population was 312 MTSN 1 Pangkalpinang students with a sample of 10 subjects. The sampling technique used was purposive sampling. The measuring tool used was a 49-item smoking behavior scale and the module used as an assertive training guide was the assertive training module (refusing invitations to smoke). The data processing technique used SPSS 22. From the results of the Paired Sample T Test data analysis, the coefficient p = 0.124 > 0.05, meaning there was no significant difference between before being given training and after being given assertive training. It can be concluded that providing assertive training can increase assertive attitudes in adolescents. However, in this study some factors caused no difference in influence before and after being given assertive training, including; inappropriate training methods, low motivation of young people to participate in the training, and limited discussion and training time.